Benefits of ICT in Education: Teaching-Learning Process - Lubaale , Grace (African Journal of Education,Science and Technology (AJEST), 2015)
The use of Information Communications Technology (ICT) in education and training is increasingly becoming a priority in African countries including Uganda. The paper aims at examining the benefits of ICT in education with a specific focus on teaching-learning process. The presenter used both qualitative and quantitative approaches of identifying the uses, application, relevance and impact of ICT in the teaching-learning process with specific cases in Uganda. The paper identifies and explains benefits of ICT in general and in the teaching –learning process in particular like to the learners in terms of general, motivational, independent learning and team work as well as teachers in planning and preparation. The paper identifies the barriers of ICT use as at five levels; political economy, technology, teachers, school and education system. The paper concludes that ICT is important in the teaching-learning process because it greatly enhances comprehension of the language and subject matter of learners as well as easing the work of teachers. It recommends government, education systems, learning institutions and individuals to embrace ICT holistically.